2008
DOI: 10.1007/s12105-008-0071-4
|View full text |Cite
|
Sign up to set email alerts
|

Site-Specific Molecular Signatures Predict Aggressive Disease in HNSCC

Abstract: It is known that head and neck squamous cell carcinomas (HNSCC) originating from different anatomic locations can exhibit varying behavior that is not predictable by histopathology of the primary tumor. Using a microarray containing 27,323 cDNA clones, we generated sets of gene expression profiles for 36 HNSCC primary tumors (12 oral cavity, 12 oropharynx, and 12 larynx/ hypopharynx). From these datasets, we ranked genes according to their ability to differentiate between patients whose disease progressed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 20 publications
1
33
0
Order By: Relevance
“…It seems to grow faster than other sites of the oral cavity and, more frequently metastasize to cervical lymph nodes with a poorer prognosis [10]. Moreover, an analysis of the Surveillance, Epidemiology, and End-Results (SEER) registry data for head and neck squamous cell carcinomas (HNSCC) demonstrated that site-specific differences in this entity may also be seen in the varied treatment approaches [11]. However, the causes for such differences in tumor behavior remain enigmatic.…”
mentioning
confidence: 99%
“…It seems to grow faster than other sites of the oral cavity and, more frequently metastasize to cervical lymph nodes with a poorer prognosis [10]. Moreover, an analysis of the Surveillance, Epidemiology, and End-Results (SEER) registry data for head and neck squamous cell carcinomas (HNSCC) demonstrated that site-specific differences in this entity may also be seen in the varied treatment approaches [11]. However, the causes for such differences in tumor behavior remain enigmatic.…”
mentioning
confidence: 99%
“…A number of studies have identified molecular distinctions among HNSCCs of varying anatomic origin (Rodrigo et al 2001;Belbin et al 2008;Kokko et al 2011;Lleras et al 2013). CD44 expression, for instance, was found to be predictive of 5-yr survival in primary pharyngeal and laryngeal tumors, but not in tumors arising in the oral cavity (Kokko et al 2011).…”
Section: A B Cmentioning
confidence: 99%
“…Global genomic analyses have identified molecular subsets of HNSCC, which may have prognostic implications [2,33,44,45]. The challenge has been to reproduce prognostic gene signatures.…”
Section: Molecular Techniques For Prognosismentioning
confidence: 99%
“…In addition, it has been recently shown that differences in gene expression related to aggressiveness of HNSCC disease are highly site specific. Therefore, it is plausible that specific biological mechanisms underlying tumor aggressiveness are heavily influenced by the anatomic site of the primary tumor such that different mechanisms offer advantage only within the specific environment of a single anatomic site [2].…”
Section: Molecular Techniques For Prognosismentioning
confidence: 99%
See 1 more Smart Citation